Analisis Dampak Inflasi Terhadap Profitabilitas Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Santi, Kevin Michael; Tonny Maringka; Sweetly Mumu (Jurnal Riset Manajemen dan Akuntansi, 2026)
This research aims to examine the impact of inflation on profitability, proxied by Return on Equity (ROE), in banking sector companies listed on the Indonesia Stock Exchange for the period 2019-2023. The analytical method employed is a quantitative approach, with data sourced from IDX Annual Reports and annual inflation data. All information was obtained from the official websites of the IDX and the Central Bureau of Statistics (BPS). The results of this study indicate that inflation does not have a significant impact or has a weak influence on Return On Equity. The results indicate that inflation does not have a significant impact or only exerts a weak influence on Return on Equity. These findings suggest that the banking sector is capable of withstanding inflationary fluctuations through the implementation of effective risk management strategies. One such strategy is the ability of banks to adjust lending and deposit interest rates in response to changes in inflation. Banks often have the flexibility to manage interest income and interest expenses, thereby mitigating the effects of inflation on profitability.